Proteomic landscape of Japanese encephalitis virus-infected fibroblasts. (21st September 2021) - Sharma, Kiran Bala; Chhabra, Simran; Aggarwal, Suruchi; Tripathi, Aarti; Banerjee, Arup; Yadav, Amit Kumar; Vrati, Sudhanshu; Kalia, Manjula
Abstract : Advances in proteomics have enabled a comprehensive understanding of host–pathogen interactions. Here we have characterized Japanese encephalitis virus (JEV) infection-driven changes in the mouse embryonic fibroblast (MEF) proteome. Through tandem mass tagging (TMT)-based mass spectrometry, we describe changes in 7.85 % of the identified proteome due to JEV infection. Pathway enrichment analysis showed that proteins involved in innate immune sensing, interferon responses and inflammation were the major upregulated group, along with the immunoproteasome and poly ADP-ribosylation proteins. Functional validation of several upregulated anti-viral innate immune proteins, including an active cGAS–STING axis, was performed. Through siRNA depletion, we describe a crucial role of the DNA sensor cGAS in restricting JEV replication. Further, many interferon-stimulated genes (ISGs) were observed to be induced in infected cells. We also observed activation of TLR2 and inhibition of TLR2 signalling using TLR1/2 inhibitor CU-CPT22-blocked production of inflammatory cytokines IL6 and TNF-α from virus-infected N9 microglial cells. The major proteins that were downregulated by infection were involved in cell adhesion (collagens), transport (solute carrier and ATP-binding cassette transporters), sterol and lipid biosynthesis. Several collagens were found to be transcriptionally downregulated in infected MEFs and mouse brain. Collectively, our data provide a bird's-eye view into how fibroblast protein composition is rewired following JEV infection.